2020
DOI: 10.17352/ojbs.000016
|View full text |Cite
|
Sign up to set email alerts
|

Pineapple juice preservation by pulsed electric field treatment

Abstract: Being the source of essential minerals, vitamin, and diversity to diet, the demand for consumption of fruits is ever increasing. Among them, many fruits are reach in phenolic compounds, carotenoids, and vitamin C or ascorbic acid, which have huge antioxidant potential and whose intakes are highly encouraged due to their role in reducing cancer, cardiovascular, and neurological diseases [1]. Since the availability of fruits varies from place to place and season to season, consumption of their preserved version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Based on the total microbial count, Abu et al. (2020) reported that PEF (13 kV/cm)‐treated pineapple juice had a shelf life of 10 days when stored at −20°C. However, the authors have claimed that increasing the electric field intensity above the critical value will improve the shelf life of the juice.…”
Section: Shelf Life Of Nonthermally Treated Pineapple Juicementioning
confidence: 99%
See 2 more Smart Citations
“…Based on the total microbial count, Abu et al. (2020) reported that PEF (13 kV/cm)‐treated pineapple juice had a shelf life of 10 days when stored at −20°C. However, the authors have claimed that increasing the electric field intensity above the critical value will improve the shelf life of the juice.…”
Section: Shelf Life Of Nonthermally Treated Pineapple Juicementioning
confidence: 99%
“…Abu et al. (2020) reported that the aerobic mesophile population (total plate count) decreased from 150 × 10 3 to 120 × 10 3 CFU/ml at a PEF strength of 9 kV/cm, and it reached the lowest value of 35 × 10 3 CFU/ml at 13 kV/cm field strength. The applied field strength of 13 kV/cm could not reach the transmembrane of a microbial cell which eventually increased the cell resistance or reactivated the bacteria after PEF treatment.…”
Section: Nonthermal Processing Of Pineapple Juicementioning
confidence: 99%
See 1 more Smart Citation
“…Several processing technologies have been applied to fruit juices, such as classical pasteurization, ohmic heating, microwave heating, thermosonication, pulsed electric fields (PEF), light treatment, supercritical carbon dioxide, and high hydrostatic pressure (HHP). For instance, PEF treatment improves shelf life of pineapple juice without compromising nutritional and antioxidant values [10]. These emerging technologies have the potential to preserve the freshness of pineapple juice.…”
Section: Introductionmentioning
confidence: 99%
“…Meskipun baru-baru ini, penggunaan High PEF telah diperluas ke pengolahan bahan padat seperti proses pretreatment daun minyak atsiri. Proses PEF melibatkan penerapan semburan pendek listrik lapangan ke sampel yang ditempatkan di antara dua elektroda yang menyebabkan permeabilitas-mungkin reversibel atau tidak dapat diubah tergantung pada parameter proses-membran (Yousuf, et al, 2020).…”
Section: Pendahuluanunclassified